Superspin glass behavior of a nonstoichiometric lanthanum manganite LaMnO3.13 - Sankar, C. R.; Joy, Pattayil Alias (Physical Review B, 2005)
Aging and memory effects are observed in an oxygen nonstoichiometric lanthanum manganite LaMnO3.13 from time-dependent dc magnetic measurements by employing various cooling protocols. The results can be best described by the superspin glass model of interacting magnetic nanoparticles system. The possible origin of such a behavior is the confinement of interacting small magnetic clusters formed as a result of the formation of manganese vacancies, along with the random distribution of tetravalent manganese ions in the lattice.